(untitled) - Thijs, Johannes Pieter (Wageningen, 1998)
Content: general introduction; analysis of meiotic recombination in maize, alnalysis of mitotic recombants.
Keywords: Gene targeting,Di truyền tiến hóa; Research,Nghiên cứu